PENGARUH KEBERAGAMAN GENDER, DIVERSIFIKASI BISNIS, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Suripto, Suripto; Aini, Nur (LPPM Universitas Bina Bangsa, 2024)
This study aims to analyze the influence of Gender Diversity, Business Diversification, and Corporate Social Responsibility on Financial Performance with Good Corporate Governance as a moderating variable. The sampling technique uses a saturated sample. This type of research is quantitative associative using secondary data based on financial reports for the period of five years from 2018-2023 which were taken from the website of the Indonesia Stock Exchange and the respective company websites. The total sample obtained was 160 companies. The data analysis technique used is panel data regression analysis using Eviews 12 software. Based on the results of the study, it can be concluded that partially Gender Diversity does not have an effect on Financial Performance, while Business Diversification and Corporate Social Responsibility have an effect on Financial Performance. Based on the analysis through moderated regression analysis, Good Corporate Governance does not moderate the influence of Gender Diversity, Business Diversification, and Corporate Social Responsibility on Financial Performance